PENGARUH BEBERAPA KOMPOSISI ALKALI DAN SERBUK JAHE MERAH (Zingiber officinale Roch.Var.Rubbrum) TERHADAP KUALITAS SABUN PADAT BERBAHAN VIRGIN COCONUT OIL - Mahmudah (JASA PADI, 2018)
This research was aimed to know the effect of some alkali composition and red ginger powder (Zingiber Officinale Roch. Var Rubrum) to the quality of the solid soap made from Virgin Coconut Oil (VCO). The method used in this experimental research is to manipulate the formulation of ginger powder soap preparation and observation of soap solid quality through free alkali analysis, measurement of acidity degree and organoleptic test based on SNI no. 06-3532-1994. The result of this research showed that the lowest free alkali content of soap bath was 0.36% and the highest was 0.8%, while the SNI provision was 0.1%, the resulting solid soap was not yet feasible to use, the degree of acidity (pH ) on solid soap is 8-9, and it in accordance with the provisions of SNI. The greater the amount of ginger powder given, the more rough the texture, the smell of ginger and the color is more brown depending on the composition of ginger powder used.